Integrated electric vehicle design and simulation: Combining a mechanical and electrical model using Simscape/Multibody - Jbari, Hatim; Askour, Rachid; Idrissi, Badr Bououlid (Institute of Advanced Engineering and Science, 2024)
This paper presents a novel methodology for modeling and implementing an electric vehicle (EV) simulation model using the Multibody approach. The proposed method provides a robust solution for studying EV performance, taking into consideration the dynamic behavior of its complex mechanical system. The mechanical design was carried out using SOLIDWORKS software and then exported to the Simscape/Multibody platform. This process was performed to combine the obtained mechanical design with an electrical model, developed using the Simscape and MATLAB/Simulink toolbox, in the same simulation platform. The proposed EV is powered by an electromechanical PowerDrive based on a permanent magnet synchronous machine (PMSM), supplied by a hybrid energy storage system (HESS). The implemented HESS, operating in a fully active topology, is controlled by a deterministic rule-based energy management system (EMS). To evaluate the proposed model performance, simulations were conducted under ECE-15.